Proceedings of the 2013 Conference on Internet Measurement Conference 2013
DOI: 10.1145/2504730.2504755
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the HTTPS certificate ecosystem

Abstract: We report the results of a large-scale measurement study of the HTTPS certificate ecosystem-the public-key infrastructure that underlies nearly all secure web communications. Using data collected by performing 110 Internet-wide scans over 14 months, we gain detailed and temporally fine-grained visibility into this otherwise opaque area of security-critical infrastructure. We investigate the trust relationships among root authorities, intermediate authorities, and the leaf certificates used by web servers, ulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
188
4
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(199 citation statements)
references
References 13 publications
5
188
4
2
Order By: Relevance
“…The recommended SHA256 (with RSA encryption) signing algorithm, has replaced SHA1 more so far for leaf certificates (72.3% SHA256) than authority certificates (42.8% SHA256). Although we observed improvements compared to the 98.7% share of SHA1 that Durumeric et al [7] observed in 2013, there is still a long way to go. While decisions by Mozilla, Microsoft, and Google, for example, to phaseout SHA1 (e.g., not showing a padlock symbol or to various degrees blocking SHA1 usage) may speed up this process, there have been setbacks in the outphasing as some of the browser companies have softened their decisions, including Mozilla re-enabling support for SHA1 in Firefox.…”
Section: Trust Relationship Analysiscontrasting
confidence: 82%
See 1 more Smart Citation
“…The recommended SHA256 (with RSA encryption) signing algorithm, has replaced SHA1 more so far for leaf certificates (72.3% SHA256) than authority certificates (42.8% SHA256). Although we observed improvements compared to the 98.7% share of SHA1 that Durumeric et al [7] observed in 2013, there is still a long way to go. While decisions by Mozilla, Microsoft, and Google, for example, to phaseout SHA1 (e.g., not showing a padlock symbol or to various degrees blocking SHA1 usage) may speed up this process, there have been setbacks in the outphasing as some of the browser companies have softened their decisions, including Mozilla re-enabling support for SHA1 in Firefox.…”
Section: Trust Relationship Analysiscontrasting
confidence: 82%
“…We also use passive measurements by Holz et al [6] (published in 2011) and by Durumeric et al [7] (published in 2013), together with our own measurements, as reference points for a longitudinal discussion. In addition to complementing these studies with more recent data points and a tutorial-style overview of the landscape, we also present complementary new analyses based on our novel session-based labeling, for example, which allows us to compare and contrast the heterogeneous security offered to both mobile and stationary devices.…”
Section: E Related Workmentioning
confidence: 99%
“…They revealed a great number of invalid certificates and certificates shared among a large number of hosts. The work of Holz et al was followed by the work of Durumeric et al [11] which focused on an assessment of certification authorities. The SSL/TLS protocol and its applications are continuously analysed by Qualys SSL Lab [12].…”
Section: State-of-the-artmentioning
confidence: 99%
“…The subject of certificate validation for HTTPS has been investigated by various other studies [42], [25], [22]. In our Common Name (Issuer Common Name) …”
Section: Tls Certificatesmentioning
confidence: 99%
“…We used techniques and tooling provided by the authors of [36] for computation of vulnerable moduli. A similar analysis was performed on datasets for HTTPS in [22].…”
Section: ) Self-signed Certificatesmentioning
confidence: 99%